Are ESG Female? The Hidden Benefits of Female Presence on Sustainable Finance - Bosone, Costanza; Bogliardi, Stefania Maria; Giudici, Paolo (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2022)
Though gender equality has been at the centre of debate over the last decades, a number of benefits concerning the impact of female directors on corporate performance are still overlooked. Particularly, the link that seems to exist between female directors and sustainable finance has received limited attention. We investigate the impact of an enhancement in female presence, meant as women in decision-making positions, on a firm’s performance both in financial and sustainability terms. The goal is to contribute to the literature streams on gender economics and on sustainable finance.Most research on sustainable finance and its impact on corporate governance rely only on aggregate ESG ratings for their results. Such scores are typically a black-box, with financial providers supplying little information about their methodology. Our analysis not only develops disaggregate scores for each dimension, but also provides motivation for the measurement of gender equality by means of specific indicators, such as the number of female directors, going beyond the bare (S) or (G) rating. ESG ratings and specific indicators of gender equality were retrieved from the well-known Bloomberg provider. Relying on a dataset concerning European companies, we empirically show that an increase in gender equality has a positive effect on a firm’s financial performance and on its share of sustainable investments.